Anticancer properties of soy-based tempe: A proposed opinion for future meal - Nurkolis, Fahrul; Qhabibi, Faqrizal Ria; Yusuf, Vincentius Mario; Bulain, Stanley; Praditya, Ghevira Naila; Lailossa, Deogifta Graciani; Mahira, Msy Firyal Nadya Al; Prima, Eka Nugraha; Arjuna, Tony; Rahayu, Shilfiana; Gunawan, William Ben; Kartawidjajaputra, Felicia; et al. (Frontier, 2022)
Cancer is in the second rank of leading causes of mortality around the world in 2020, with around 10 million death cases, just behind heart disease, as well as approximately 250 million disability-adjusted life years (DALY) due to cancers (1). The most common form of deadly cancer is tracheal, bronchus, and lung cancer generally, and the number is greater for males. However, women also possess the threat of female-specific cancer, including breast (higher in women, but also happens in men), cervical, ovarian, and uterine cancer. This is also burdened by low-middle socioeconomic status (1, 2). In 2019, the number of new cancer incidents reached around 23.6 million cases, which increased from the 2010 incidence (18.7 million cases) (1). The risk factor includes smoking, unhealthy diets, and pollution, which increases the risks of developing cancer in the future (3). There have been several cancer treatment options in recent years, such as surgery, radiation, and chemotherapy.